2020
DOI: 10.1186/s40816-020-00228-2
|View full text |Cite|
|
Sign up to set email alerts
|

An exploratory analysis on the toxicity & safety profile of Polyherbal combination of curcumin, quercetin and rutin

Abstract: Background Curcumin, quercetin and rutin are flavonoids having strong antioxidant potential, individually used in treatment of numerous ailments. The safety assessment of each of them is already established but no toxicological assessment has been done that would guarantee the safe use of these three flavonoids when used as a polyherbal combination (PHC). The aim of this study to evaluate the possible toxicological effect of polyherbal combination of these three flavonoids in female Swiss albin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…showed that quercetin seems to be safe at a dose level of 2000 mg/kg, and the LD50 is considered to be >2000 mg/kg. Any pharmaceutical drug or compound with an oral LD50 higher than 1000 mg/kg could be considered safe 8,9 . Thus, data from the literature supports the safe use of quercetin in the concentration proposed in this study.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…showed that quercetin seems to be safe at a dose level of 2000 mg/kg, and the LD50 is considered to be >2000 mg/kg. Any pharmaceutical drug or compound with an oral LD50 higher than 1000 mg/kg could be considered safe 8,9 . Thus, data from the literature supports the safe use of quercetin in the concentration proposed in this study.…”
Section: Introductionsupporting
confidence: 73%
“…It is abundant in foods such as fruits and vegetables. The in vivo and in vitro genotoxicity, acute, subchronic, and chronic toxicity, and carcinogenicity studies of quercetin exposed that at predictable dietary intake levels, it does not result in adverse health effects 8,9 . Recently, Tiwari et al 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of plasma should be maintained up to 2–8 °C during handling. The fresh separated plasma was utilized for the evaluation of various biochemical parameters, the remaining were divided into 0.5 mL aliquots and were stored at −20 °C [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…(1) Enhances glucose uptake through the activation of AMPK signaling pathway in skeletal muscle cells [61,62] (2) Protects the β-cells from apoptosis [63] (3) Enhances insulin receptor beta-subunit, GLUT4, and tissue insulin sensitivity [64] (4) Inhibitory effect on α-glucosidases [65] (5) Inhibits gluconeogenesis through the upregulation of AMPK [66] Sambucus nigra L. [67] Madagascar periwinkle [68] Catharanthus roseus [68] Elaeodendron croceum [68] Fisetin…”
Section: Ohmentioning
confidence: 99%
“…It is reported that rutin can alter Ca 2+ uptake in isolated pancreatic islets, followed by an increase in the uptake of Ca 2+ . Tiwari et al have documented those previous studies that showed rutin is safe at a concentration of 2000 mg/kg and the intake of rutin from dietary sources will not cause any toxicity effects [ 61 ]. Rutin is widely distributed in plants, for example, Ruta graveolens , Morus alba , asparagus, and buckwheat [ 62 ].…”
Section: Flavonoids Of Various Plants and Their Hypoglycemic Effectsmentioning
confidence: 99%